Mortality pattern in a glass producing area in SE Sweden. Issue 6 (June 1985) - Wingren, G; Axelson, O
Abstract : Because of discharges, mainly of lead, from glassworks in an otherwise rural and unpolluted area in southeast Sweden the population became concerned about the potential risks of cancer and an epidemiological study was requested. The total and the specific cancer mortality in the three parishes around the glassworks were found to be approximately normal, both by comparison with national death rates and the death rates of another, similarly rural, area. More interesting results, however, were obtained in several case-referent studies also undertaken to study mortality from specific cancer sites and cardiovascular disease with regard to employment in the glassworks. A significant excess of deaths from stomach cancer, especially in glassblowers, lung cancer, and cardiovascular disease was observed among the glassworkers. Occupational exposures in the glassworks, especially to arsenic, may be of aetiological importance.